2012
DOI: 10.1002/pssb.201100723
|View full text |Cite
|
Sign up to set email alerts
|

Is there a common theme behind the correlated‐electron superconductivity in organic charge‐transfer solids, cobaltates, spinels, and fullerides?

Abstract: We posit that there exist deep and fundamental relationships between the above seemingly very different materials. The carrier concentration-dependences of the electronic behavior in the conducting organic charge-transfer solids and layered cobaltates are very similar. These dependences can be explained within a single theoretical model, the extended Hubbard Hamiltonian with significant nearest neighbor Coulomb repulsion. Interestingly, superconductivity in the cobaltates seems to be restricted to bandfilling … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…We have recently shown how it may be possible to construct such a framework for the CTS. [51][52][53][54] In this picture, the κ-(ET) 2 X and other dimerized CTS should be described in terms of the underlying 1 4 -filled band as with the other CTS superconductors. 51,52 n the presence of strong dimerization and relatively weak frustration, AFM wins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently shown how it may be possible to construct such a framework for the CTS. [51][52][53][54] In this picture, the κ-(ET) 2 X and other dimerized CTS should be described in terms of the underlying 1 4 -filled band as with the other CTS superconductors. 51,52 n the presence of strong dimerization and relatively weak frustration, AFM wins.…”
Section: Discussionmentioning
confidence: 99%
“…Even more interestingly, we have pointed out that there exist several frustrated strongly correlated inorganic 1 4 -filled superconductors that can perhaps be described within the same model. [52][53][54] Finally, the experimental observation of AFM 60 in expanded fullerides A 3 C 60 has led to the modeling of these compounds in terms of a 3D nondegenerate 1 2 -filled band Hubbard model. 61 The threefold degeneracy of the lowest antibonding molecular orbitals in C 60 is removed by Jahn-Teller instability.…”
Section: Discussionmentioning
confidence: 99%
“…The question that we started with -what is the minimal model that describes the CTS -then continues to be relevant. The only choice appears to be the interacting frustrated 1 4 -filled band model [27], which has the added advantage that it applies equally well to both the dimerized κ-(ET) 2 X and Z[Pd(dmit) 2 ] 2 and the undimerized θ-(ET) 2 X which show CO-SC (as opposed to AFM-SC) transitions (recall that the charge carrier density per molecule is the same in these two classes of CTS). In recent work [28,29] we have shown that a frustrationdriven AFM-spin singlet transition occurs within the dimerized interacting 1 4 -filled band model, where the spin singlet state also exhibits CO.…”
mentioning
confidence: 99%
“…Correlated-electron superconductivity (SC) continues to be one of the most challenging problems in condensed matter physics. Even as the large majority of investigators in this research area have focused on cuprates and iron-based superconductors (and more recently, ruthenates), it is now widely recognized that there exist many other unconventional or correlated-electron superconductors, although with lower superconducting critical temperature T c [1][2][3][4][5][6][7][8][9]. Superconducting organic charge-transfer (CT) solids hold a special place in this context, as SC in CT solids was discovered significantly prior to the discovery of the phenomenon in the cuprates [10].…”
Section: Introductionmentioning
confidence: 99%